Liver Cirrhosis of Unknown Etiology and Its Predictors in Eastern Ethiopia - Mekuria AN; Nedi T; Gong YY; Abula T; Engidawork E (Dove Medical Press, 2024)
Abraham Nigussie Mekuria,1 Teshome Nedi,1 Yun Yun Gong,2 Teferra Abula,1 Ephrem Engidawork1 1Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2School of Food Science and Nutrition, University of Leeds, Leeds, UKCorrespondence: Ephrem Engidawork; Teferra Abula, Email ephrem.engidawork@aau.edu.et; abula_teferra@yahoo.comBackground: The global burden of liver cirrhosis is increasing, with 2.1 million incident cases and nearly 1.5 million deaths in 2019. Despite the enormous progress in our understanding of the etiology of liver cirrhosis, significant cases of the disease have been reported in Eastern Ethiopia due to unidentified causes. Hence, this study aimed to identify predictors of liver cirrhosis of unknown etiology in Eastern Ethiopia.Methods: A score of 7 out of 11 possible points on the ultrasound-based cirrhosis scale was used as a diagnostic criterion to include 127 liver cirrhosis patients. The study participants' demographic, dietary, lifestyle, and clinical data were gathered using a structured questionnaire and standardized reporting forms. The associations between the outcome (known and unknown etiology) and independent variables were modeled using binary logistic regression analysis.Results: The etiology of liver cirrhosis was known in only 23% of patients and attributed to hepatitis B virus (21%), hepatitis C virus (0.8%), and alcohol abuse (0.8%). Sorghum consumption as a staple food (adjusted odds ratio (AOR) =3.8; 95% CI: 1.2, 12.5), splenomegaly (AOR = 4.0; 95% CI: 1.1, 14.4), and a family history of liver disease (AOR = 0.24; 95% CI: 0.06, 0.91) were significantly associated with liver cirrhosis of unknown etiology.Conclusion: Sorghum consumption was found to be the determinant factor of liver cirrhosis of unknown etiology, suggesting it as a possible source of exposure to aflatoxin B1.Keywords: liver cirrhosis, unknown etiology, sorghum, splenomegaly, family history of liver disease, Ethiopia